The psychometric properties of parental stress scale-Turkish form - Aslan Gördesli, Meltem; Aydın Sünbül, Zeynep (Turkish Psychological Counseling and Guidance Association, 2021)
The aim of this study is to adapt the Parental Stress Scale developed by Berry and Jones (1995) to Turkish parents. The study was carried out with 534 parents. The scale's validity was examined with exploratory and confirmatory factor analysis. The discrimination, difficulty, and informativeness of the items were examined using the Item Response Theory. Independent samples t-test between the lower and upper 27% scores was performed to test the discrimination of the scale. It has been found that there was a negative relationship between the Parental Stress Scale and the Satisfaction with Life Scale scores, and a positive relationship between the Parental Stress Scale and the Perceived Stress Scale scores. The internal consistency coefficient of the scale and subscales were found to be between .70 and .81 respectively. The results showed that Parental Stress Scale is a valid and reliable tool for measuring parental stress level of Turkish parents.
Ebeveyn stres ölçe?i türkçe formu'nun psikometrik özellikleri
Keywords: Item Response Theory; Parental Stress Scale; Reliability; Validity